Critique of consequentialist moral absolutism - García Gibson, Francisco (Estudios de Filosofía, 2018)
In this work, I assess critically three arguments in favor of moral absolutism. Perhaps surprisingly, these arguments justify absolutism because of its consequences. The first argument point out from certain cognitive biases in orden to show that treating moral norms as absolute maximizes our conformity with these norms. The second argument holds that we must deal with a right as absolute when it is not possible to compensate the infraction of that right; otherwise, rights would lose all practical relevance. The third argument starts o with the intrinsic value of special relationships, like friendship, to show that special relationships will be undermined if we do not treat special obligations as absolute. The three arguments fail because they do not show that treating certain moral norms as absolute is neither necessary nor suffcient to accomplish the important consequences that the arguments identify.